SiCST1, a novel plant-specific protein of foxtail millet, confers cold stress tolerance in plants - Fan Yang; Jiaqi Qiao; Xiao Zhang; Zhuoya Zhang; Dongao Huo; Dongao Huo (Frontiers in Plant Science)
Foxtail millet (Setaria italica) is a significant cereal crop, but its yield is limited by extreme temperature, particularly cold stress. In this study, we identified a novel plant-specific gene, SiCST1 (Cold Stress Tolerance in Setaria italica 1) in foxtail millet, through transcriptome deep sequencing (RNA-Seq) of cold-stressed seedlings. We generated a CRISPR/Cas9-mediated knockout mutant of rice homolog of SiCST1 (designated oscst1). Compared to wild-type rice, oscst1 mutant seedlings exhibited cold sensitivity with a 46% survival rate reduction under cold stress. This impaired cold stress tolerance was rescued by complementation with SiCST1, indicating the vital role of SiCST1 in cold stress tolerance. SiCST1 consists of a single exon and contains a predicted ribonuclease H-like domain. Further analysis revealed that SiCST1 was significantly up-regulated in response to cold stress and was localized in nucleus. Additionally, our findings suggested that SiCST1 interacted with the OVATE family protein SiOFP1. The lamina joint bending assays were employed to investigate whether mutation of rice homolog of SiCST1 affected the brassinolide (BR) signaling pathways. It was found that oscst1 exhibited insensitivity to exogenous BR treatment. We propose a regulatory mechanism in which SiCST1 interacted with SiOFP1 to release its inhibition of BR signaling transcription complex, thereby activating BR signaling pathways and conferring cold stress tolerance. Our study provides evidence that SiCST1 is a novel plant-specific protein with an essential function involved in cold stress resistance in foxtail millet.